Institutionalism and Economic Development in Peru: A Senior Executive’s View from the Application of Augmented Fuzzy Cognitive Maps - Ortigueira-Sánchez, Luis Camilo; Gimbert Ràfols, Xavier (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología, 2018)
This article analyzes key factors that have contributed to the growth and economic development of Peru during the last fifteen years. An augmented fuzzy cognitive map (FCM) methodology has been applied to a sample of senior executives from top Peruvian companies. The results revealed a series of key aspects that explain the development achieved in the country and were compared with those of previous studies examining institutional influence over competitiveness.